Global perspectives on mentoring : transforming contexts, communities, and cultures - Kochan, Frances K.; Pascarelli, Joseph T. (Perspectives in mentoring., 2003)
This book will examine mentoring from a global perspective in an effort to discover the commonalties and differences, not only in diverse fields of practice, but across a wide range of contextual Place your subscription or standing order today! settings. Each chapter of the book will contain an overview of the program, problems encountered and solutions to them, benefits, outcomes, impact, and thoughts for reflection and consideration. The editor will examine common themes and explore their cross cultural implications. The volume is intended for those interested in the concept of mentoring in any professional setting and culture. It will provide important insights into how to create a mentoring program, strategies for overcoming problems, and methods for assessing outcomes and impact.